The Teaching of Pre-Existing National Polish Law in the New Kingdom of Poland - Wiśniewska, Dorota (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The changes in the social and economic system taking place in the Kingdom of Poland prompted the need for legal education at the university level. The functioning of universities dealing with teaching in this area, however, met various obstacles, mainly due to the reluctance of the central authorities of the Russian Empire.At the universities established in the following years, the aim was not only to prepare future lawyers in practice, but also to implement a broader model of education. Therefore, among other fields, the old Polish law was tutored, which gradually ceased to be binding, and finally became a historical law.